The value relevance of corporate responsibility reporting in South Africa - Marcia, Adrian Michael (My University, 2015)
This dissertation assesses whether corporate responsible reporting (CRR) is value relevant in determining the market value of a JSE listed equity. In doing so, relevant literature surrounding value relevance is explored and, in addition to the theoretical underpinnings, statistically assessed to add robustness to the value relevance model. This research adds to the volume of academic literature surrounding CRR in a South African context. Using a normative metric, which incorporates recent changes to the South African corporate governance landscape, namely King-III, this paper further explores elements of South African value relevance. The aforementioned assessment is based off a modified Ohlson (1995) model – allowing an incremental assessment between the predictive capacities of a model which incorporates purely financial information versus one which includes both CRR and financial information. Value relevance, in the context of this study, is the increase in the predictive power of the model when CRR information is added. The above assessment is based on quantitative findings, which assess the relationship between the predictor variables, opening book value of equity, net income through the period and CRR information, on the dependent variable, market value of equity at the end of the period. Therefore, this research does not attempt to explain the underlying social phenomena which create the statistical relationship. The findings of the dissertation, after satisfying all the relevant assumptions of hierarchical linear regression, indicate the CRR, when based off the normative metric, does not add to the predictive capacity of a South African value relevance model.
Thesis (M. Com. (Accountancy))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Accountancy, 2014.